Traditional Media Use in Forest Conservation Support Communication (FCSC) among Local Residents in Protected Areas in Southwestern Nigeria (2003)
This paper examined the potential of forest conservation support communication along traditional media in use for agricultural information dissemination in and around two reserved sites: Old Oyo National Park, Oyo and Oluwa forest reserve in Ondo State. Results show that the reliability of Forest Conservation Support Information (FCSI) sources depends on access to media among respondents (Pearson's ,X2= 338.7; df = 160; Pr ≤ 0.000). So also, appropriateness determines the relevance of traditional media in Old Oyo National Park environment to FCSC (Pearson's X2= 176. 47; df = 60; Pr ≤ 0.00). This was however not the case in 0luwa forest reserve enclaves (Pearson's X2 = 29 595: df = 28; Pr > 0.383) Here, the perception of inhabitants on appropriateness of media for FCSC does not translate to their being relevant for the same purpose. But the relevance of traditional communication to present-day development challenges was found to be very significant in the study sites. Only 2.5% and 7% of inhabitants of Oluwa forest enclaves and Old Oyo National Park environment respectively considered trado communication as irrelevant to forest conservations support communication. Analysis of variance on traditional media accessed in the two study sites also revealed no variation (F = 3.01, df = 244; p> 0.5) Furthermore, in Oluwa Forest enclaves, 88.75% of the respondents' perceived trado communication as complementing other information sources, while the rest opined that it's use alone could effect and sustain development initiatives. However none of the respondents in the two sites is of the view that the use of traditional communication media should be relegated to the background in FCSC it is therefore recommended that effective indigenous media should be adopted and empowered to ensure that development initiatives are not wrongly imbibed. So also, traditional institutions in the study area must be identified and empowered with sustainable forest conservation information and technologies.